Composite Modifiers to Improve the Rheological Properties of Asphalt Binders - Yalcin, Beyza Furtana; Bakir, Esma; Yalcin, Erkut; Yilmaz, Mehmet (Asce-Amer Soc Civil Engineers, 2024)
For the last 20 years, researchers have been looking for ways to modify asphalt binders to improve their rheological and thermophysical properties. The application of composite modifiers to enhance the rheological properties of asphalt binders offers a potential remedy for this significant issue. Because of this, this study looked at how composite modifiers affected the plain binder's rheological characteristics. This study examined the rheological properties of unmodified and modified binders using a variety of formulations to blend modifiers including linear styrene-butadiene-styrene (SBS), radial SBS, Elvaloy, and polyphosphoric acid (PPA). The effect of PPA on the properties of polymer-added binders at low temperatures was investigated. Additionally, modifications using PPA aim to reduce the polymer content. Based on traditional performance classification (PG) and multiple stress creep recovery (MSCR) systems, original, rolling thin film oven-aged, and pressure aging vessel-aged binders were divided into three groups using a dynamic shear rheometer (DSR). The performance of binders at low temperatures was also assessed using the bending beam rheometer (BBR). All of the study's additions were discovered to have enhanced the neat binder's high-temperature capabilities. The elastic property of the neat binder was increased by the addition of Elvaloy and PPA. Results showed that, although the PPA modifier reduced the hardness of neat asphalt binder at low temperatures, other additives did not show significant effects on the hardness of the binder. The MSCR procedure was successfully utilized to grade all of the binders, but it appears that some binders and conditions do not fit the MSCR protocol's percent difference criterion. According to the study's findings, SBS can be replaced by 611 elastomer to enhance the performance of binders at high and moderate temperatures.
Keywords: Styrene-butadiene-styrene (SBS); Polyphosphoric acid (PPA); Rheology; Composite modifier